A decade of Oyo State 1976 - 1986 - Ministry of Information, Ibadan (Ibadan : Ministry of Information, 1986)
This publication highlights the State's main achievements from 1976 - 1986.
rpm 12/04/2017
Loans
Keywords: Administration; Government; Social -- Economic Development; Ibadan, Nigeria